Pengaruh Beban Kerja dan Disiplin terhadap Kinerja Pegawai pada Rumah Sakit Tk III dr. Bratanata Kota Jambi - Emil, Muhammad; Ardy, Ardy (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study aims to determine the effect of workload and discipline on employee performance at dr. Bratanata General Hospital, Jambi City. The research method used is descriptive quantitative. The study population was all 304 employees of dr. Bratanata General Hospital, Jambi City, with a sample of 75 respondents determined using the Slovin formula. Data analysis techniques used include validity tests, reliability tests, classical assumption tests, multiple linear regression, correlation coefficients, determination coefficients, F tests, and t tests. The results of the study indicate that workload and discipline simultaneously and partially have a significant effect on employee performance at dr. Bratanata Hospital, Jambi City.